Happiness and economics : how the economy and institutions affect well-being - Frey, Bruno S.; Stutzer, Alois (Princeton University Press, 2002)
"Curiously, economists, whose discipline has much to do with human well-being, have shied away from factoring the study of happiness into their work. Happiness, they might say, is an ''unscientific'' concept. This is the first book to establish empirically the link between happiness and economics--and between happiness and democracy. Two respected economists, Bruno S. Frey and Alois Stutzer, integrate insights and findings from psychology, where attempts to measure quality of life are well-documented, as well as from sociology and political science. They demonstrate how micro- and macro-economic conditions in the form of income, unemployment, and inflation affect happiness. The research is centered on Switzerland, whose varying degrees of direct democracy from one canton to another, all within a single economy, allow for political effects to be isolated from economic effects